Lecturer Performance Information Systems Based on IAPS 4.0 - Yang Agita Rindri Yang; Boy Rollastin (Manutech : Jurnal Teknologi Manufaktur, 2021)
Currently, the lecturer performance data based on IAPS 4.0 at Polman Babel are still not integrated yet and still collected in Microsoft Excel. This study aims to develop Lecturer Performance Information Systems Based on IAPS 4.0 that can assist the preparation and management of IAPS 4.0-based lecturer performance. This study follows the Systems Development Life Cycle includes planning and preparation, system analysis, system design, development,  testing, and deployment. The system is developed using PHP programming language, MySql database, Codeigniter Framework, Bootstrap Framework for CSS, and the Guzzle library to create a REST Client that accesses the Google Scholar REST API. System testing in this study uses black-box testing to test system functionality. The functionality testing shows that the functionality of the system is 100% successful and accepted by stakeholders.